siRNA Versus miRNA as Therapeutics for Gene Silencing - Jenny K W Lam; Michael Y T Chow; Yu Zhang; Susan W S Leung (Elsevier, 2015)
Discovered a little over two decades ago, small interfering RNAs (siRNAs) and microRNAs (miRNAs) are noncoding RNAs with important roles in gene regulation. They have recently been investigated as novel classes of therapeutic agents for the treatment of a wide range of disorders including cancers and infections. Clinical trials of siRNA- and miRNA-based drugs have already been initiated. siRNAs and miRNAs share many similarities, both are short duplex RNA molecules that exert gene silencing effects at the post-transcriptional level by targeting messenger RNA (mRNA), yet their mechanisms of action and clinical applications are distinct. The major difference between siRNAs and miRNAs is that the former are highly specific with only one mRNA target, whereas the latter have multiple targets. The therapeutic approaches of siRNAs and miRNAs are therefore very different. Hence, this review provides a comparison between therapeutic siRNAs and miRNAs in terms of their mechanisms of action, physicochemical properties, delivery, and clinical applications. Moreover, the challenges in developing both classes of RNA as therapeutics are also discussed.